SISTEM INFORMASI PEMBUATAN SURAT KETERANGAN TIDAK MAMPU BERBASIS WEBSITE - Ifan Prasetyariansyah; Muqtadir, Faidhul; A. Hamdani (Jurnal Riset Sistem Informasi, 2025)
The purpose of this study is to develop and build an online information system for making a Certificate of Inability to Pay (SKTM) to overcome the problem of manual service procedures in Bercak Village. The approach used in building this system is the waterfall model which includes the stages of needs analysis, design, implementation, testing, and maintenance. Data collection is carried out through observation, interviews, literature reviews, and documentation. Through this system, the community can apply for SKTM online, making it easier for administrators to verify and village heads to issue SKTM. In addition, WhatsApp is also used to send notifications when the letter has been completed. The results of the blackbox test show that each feature runs as expected. This method is believed to be able to improve the accuracy, efficiency, and transparency of village administration services.